Addressing the Topic of the Great Patriotic War of 1941 – 1945 in Foreign Language Classes in University Settings as a Tool for Fostering Patriotism in Younger Generation - Bagretsova N. V. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
emphasizing the importance of passing on the memory of the Great Patriotic War to the younger generation in order to instill in them devotion to their native country, the article proposes to address this topic in foreign language classes in university settings as one of the ways to achieve this aim. Various aspects of topic-based instruction ensuring the development of the necessary communicative competencies of students are considered. The article focuses on authentic tasks and online tools for autonomous work on them: dictionaries, machine translation tools and speech synthesizers.
Keywords: Великая Отечественная война; иностранный язык; foreign language; Great Patriotic War; Вторая мировая война; World War II; аутентичные задания; тематический подход; онлайн-средства изучения языка; topic-based instruction; authentic tasks; online language learning tools